KELAYAKAN SISTEM PENGENDALIAN INTERN TERHADAP EFEKTIVITAS PENGELOLAAN KAS PADA PT. POS INDONESIA (PERSERO) CABANG PAREPARE - Bustam, Astri (Universitas Muhammadiyah Parepare, 2019)
This study aims to determine the internal control system on the effectiveness of cash management at PT. Pos Indonesia (Persero) Parepare Branch. This research method is qualitative. The Data Collection Techniques used in this study are observation, documentation, and interviews. Data analysis techniques in this study used descriptive qualitative research. The results showed that the internal control system on cash management at PT. Pos Indonesia (Persero) Parepare Branch is good. This can be seen from the internal control components found in the company by looking at aspects of effectiveness. The aspects of effectiveness are the duties and functions, plans or programs, as well as policies or regulations in PT. Pos Indonesia (Persero) Parepare Branch is run well, but of the three aspects there is one aspect that has not been optimally implemented properly, namely the policy or regulatory aspects, but two that have been run well. Internal control system for cash management at PT. Pos Indonesia (Persero) Parepare Branch said it was effective.